An investigation into the ecological niches and seasonal nature of Clostridium estertheticum and Clostridium gasigenes in the Irish beef farm environment. (1st October 2020) - Esteves, E.; Whyte, P.; Gupta, T.B.; Bolton, D.J.
Abstract: Blown pack spoilage (BPS) of vacuum packaged beef is caused by psychrotolerant and psychrophilic Clostridium species, primarily Clostridium estertheticum and Clostridium gasigenes . The aim of this study was to investigate the environmental niches and impact of season on these BPS Clostridium spp. on Irish beef farms. On each of five different beef farms, faecal (10), soil (5), silage (5), air (5), bedding straw (5), drinking water (5) and puddle/ditch water (5) samples were collected during Spring, Summer, Autumn and Winter and tested for C. estertheticum and C. gasigenes using culture (direct plating and enrichment) and molecular (conventional PCR and quantitative PCR (qPCR)) based techniques. C. estertheticum and C. gasigenes were detected in all sample types, with qPCR detection rates ranging from 4% to 50% and at concentrations of up to 1·5 log10 CFU per g and 3·5 log10 CFU per g, respectively. The impact of season was not clear as the results were mixed depending on the detection method used. It was concluded that BPS‐causing C. estertheticum and C. gasigenes are widely distributed in the beef farm environment. Abstract : Significance and Impact of the Study: Blown pack spoilage of vacuum packaged beef caused by Clostridium estertheticum and Clostridium gasigenes is a significant problem for the beef industry. At present, control is reliant on regular disinfection of the abattoir and equipment with sporicidal agents, but it has been suggested that preventing contamination of cattle at the source could be more effective. This study provides evidence that BPS Clostridium spp. are widely distributed on beef farms with multiple dissemination routes, prohibiting on‐farm control.